PERAN SELF EFFICACY SEBAGAI MEDIATOR ANTARA JOB RESOURCES DAN WORK ENGAGEMENT PADA DOKTER HEWAN - Puspa Putri Sajuthi; Raja O. Tumanggor; P. Tommy Y.S. Suyasa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2020)
This study explores the role of self-efficacy as a mediator between job resources and work engagement among veterinarians. Self-efficacy is seen as the degree of confidence of the veterinarian in performing their duties. Job resources is an aspect of work that individuals can use to handle the demands and challenges of their work. Job resources in this study includes opportunities for professional development and skills discretion. Opportunties for professional development refers to the opportunities provided for veterinarians to enroll in courses that can develop their veterinary knowledge. Skills discretion refers to the extent to which veterinarians acquire the opportunity to apply all their skills, both as a veterinarian and other skills such as negotiation and creativity. Participants included 32 veterinarians from X Veterinary Clinic, Jakarta. The analysis methods used were regression and bootstrapping. The results showed that self-efficacy is proven to act as a partial mediator in explaining the relationship between skills discretion and work engagement. Penelitian ini mengeksplorasi peran self efficacy sebagai mediator antara job resources dan work engagement pada dokter hewan. Self efficacy digambarkan sebagai derajat keyakinan dokter hewan dalam melakukan pekerjaannya. Job resources merupakan aspek pekerjaan yang dapat digunakan individu untuk menangani tuntutan dan tantangan pekerjaannya. Job resources pada penelitian ini digambarkan dengan opportunities for professional development dan skills discretion. Opportunties for professional development mengacu pada kesempatan yang diberikan bagi para dokter hewan untuk mengikuti kursus yang dapat mengembangkan ilmunya sebagai dokter hewan. Skills discretion mengacu pada sejauh mana dokter hewan memeroleh kesempatan untuk menerapkan segenap keterampilan yang dimilikinya baik keterampilan sebagai dokter hewan maupun keterampilan lainnya seperti negosiasi dan berkreasi. Partisipan adalah 32 orang dokter hewan di Klinik Hewan X, Jakarta. Metode analisis yang digunakan adalah regresi dan bootstrapping. Hasil penelitian menunjukkan bahwa self efficacy teruji berperan sebagai mediator parsial dalam menjelaskan hubungan antara skills discretion dan work engagement.